2019
DOI: 10.3389/fphar.2019.00409
|View full text |Cite
|
Sign up to set email alerts
|

Loganin Exerts Sedative and Hypnotic Effects via Modulation of the Serotonergic System and GABAergic Neurons

Abstract: Corni fructus, the fruit of Cornus officinalis Sieb. et Zucc., has been used as a tonic for the kidney in China for thousands of years. Loganin is one of the major constituents derived from Corni fructus. In this study, we revealed the sedative and hypnotic activity of loganin and investigated its mechanisms for the first time. Pentobarbital-induced sleep test and insomnia mice models [induced by caffeine and p-chlorophenylalanine (PCPA)] were used for the assessment of sedative and hypn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…5-HIAA is associated with analgesia and sleep. Previous studies have revealed that in animal models of insomnia or sleep deprivation, 5-HIAA levels decrease with those of 5-HT (27,28). The HTR1A gene encodes the 5-HT1A receptor, the latter of which binds to the free form of 5-HT in the synaptic space, thus mediating 5-HT function, increasing its nervous system activity and promoting sleep (29).…”
Section: Discussionmentioning
confidence: 99%
“…5-HIAA is associated with analgesia and sleep. Previous studies have revealed that in animal models of insomnia or sleep deprivation, 5-HIAA levels decrease with those of 5-HT (27,28). The HTR1A gene encodes the 5-HT1A receptor, the latter of which binds to the free form of 5-HT in the synaptic space, thus mediating 5-HT function, increasing its nervous system activity and promoting sleep (29).…”
Section: Discussionmentioning
confidence: 99%
“…Morroniside protects against cerebral ischemia/reperfusion injury by inhibiting neuron apoptosis and MMP2/9 expression (Zeng et al, 2018). Loganin exerts sedative and hypnotic effects via modulation of the serotonergic system and GABAergic neurons (Shi et al, 2019). Cornuside attenuates apoptosis and ameliorates mitochondrial energy metabolism in rat cortical neurons (Jiang et al, 2009; Jiang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The IR spectrum showed absorption bands for hydroxy (3401 cm À 1 ) and carbonyl (1687 and 1639 cm À 1 ) functionalities, respectively. Its 1 H-NMR 1 [3] and the extra carbons signals (δ(C) 38.1 (CH 2 ), 41.1 (CH 2 ), 52.9 (MeO), 71.6 (CH), 75.2 (CH), 76.6 (CH), 76.7 (C) and 175.8 (C=O)), which was closely similar to those of methyl quinate. [8 -10] confirmed that the C-1' of methyl quinate groups was connected to C-7 by an ether linkage.…”
Section: Structural Elucidationmentioning
confidence: 90%
“…is a well‐known traditional Chinese medicine used for nourishing the liver and kidney in China, which has been used for thousands of years. The chemical and pharmacological studies on the fruit of C. officinalis have been lasting for many years in our group . Recently, further chemical investigation on the title plant led two new iridoid glucosides, cornusglucoside A ( 1 ) and cornusglucoside B ( 2 ) ( Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation